EVALUASI KEBERLANJUTAN PENGELOLAAN SAMPAH KOTA PADANG: PENDEKATAN BERBASIS KEBIJAKAN PUBLIK MELALUI ANALISIS MDS-RAPFISH - Meuraksa, Irawati; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
This study aims to evaluate the sustainability of waste management in Padang City through a public policy-oriented approach using the Multi-Dimensional Scaling (MDS) method with a modified RAPFISH (Rapid Appraisal for Fisheries) framework. The evaluation covers five key dimensions of sustainability: economic, environmental, social, technological and infrastructure, and institutional. Primary data were collected through interviews with key informants, while secondary data were obtained from policy documents and relevant literature. The results indicate that all five dimensions fall into the